2014
DOI: 10.1111/j.2047-2927.2014.00234.x
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA integrity testing: big halo is a good predictor of embryo quality and pregnancy after conventional IVF

Abstract: SUMMARYSperm DNA integrity is a sperm functional parameter of male fertility evaluation. Two parameters of sperm DNA integrity were observed: DNA damage expressed as DNA fragmentation index (DFI) and percentage of the DNA undamaged spermatozoa expressed as big halo. Halosperm test was used for sperm DNA integrity determination. The aim of this study was to evaluate which DNA integrity parameter is better as an embryo quality and pregnancy prognostic parameter after the conventional IVF. We evaluated two embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 52 publications
4
40
0
1
Order By: Relevance
“…The deleterious effect of fragmented paternal DNA on embryonic viability and progression of pregnancy has been experimentally shown in mouse models [Ahmadi and Ng 1999] and similar results were also observed in human patients who opt for assisted reproductive technologies such as IVF and ICSI [Lin et al 2008;Muriel et al 2006;Robinson et al 2012;Tandara et al 2014;Tesarik et al 2004;Wdowiak et al 2015;Zhao et al 2014;Zini et al 2008]. In idiopathic cases of recurrent miscarriages too, the higher rates of sperm DNA fragmentation have been implicated, in the absence of any detectable female factor abnormality [Absalan et al 2012;Brahem et al 2011;Carrell et al 2003;Kumar et al 2012;Ramasamy et al 2015;Ribas-Maynou et al 2012;Zidi-Jrah et al 2016].…”
Section: Introductionsupporting
confidence: 55%
“…The deleterious effect of fragmented paternal DNA on embryonic viability and progression of pregnancy has been experimentally shown in mouse models [Ahmadi and Ng 1999] and similar results were also observed in human patients who opt for assisted reproductive technologies such as IVF and ICSI [Lin et al 2008;Muriel et al 2006;Robinson et al 2012;Tandara et al 2014;Tesarik et al 2004;Wdowiak et al 2015;Zhao et al 2014;Zini et al 2008]. In idiopathic cases of recurrent miscarriages too, the higher rates of sperm DNA fragmentation have been implicated, in the absence of any detectable female factor abnormality [Absalan et al 2012;Brahem et al 2011;Carrell et al 2003;Kumar et al 2012;Ramasamy et al 2015;Ribas-Maynou et al 2012;Zidi-Jrah et al 2016].…”
Section: Introductionsupporting
confidence: 55%
“…A study by Tandara and colleagues has shown that halos obtained with the Halosperm represent a prognostic parameter of good embryo quality. In their study, they found a significant correlation between large halos, good morphology embryos, scored on day three of development, and the achievement of a pregnancy [25].…”
Section: Discussionmentioning
confidence: 92%
“…Sperm DNA integrity is a functional parameter of male fertility evaluation (Tandara et al, 2014). A molecular epidemiology approach and/or the use of integrated biomarkers of sperm quality and sperm DNA damage might be useful for future research focused on the low-to-moderate dose range for diagnostic and professional exposures (Latini et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Sperm DNA integrity is a functional parameter of male fertility evaluation (Tandara et al, 2014). The sperm DNA fragmentation index (DFI) is a good prognostic marker; a higher sperm DFI may be associated with a poor successful pregnancy rate, even after assisted conception, and may be associated with recurrent loss of the fetus (Venkatesh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%